Circumstances of falls and falls-related injuries in a cohort of older patients following hospital discharge - Hill AM; Hoffmann T; Haines TP (Clinical Interventions in Aging, 2013)
Anne-Marie Hill,1 Tammy Hoffmann,2,3 Terry P Haines4,51School of Physiotherapy, Institute for Health Research, The University of Notre Dame Australia, Fremantle, WA, 2Centre for Research in Evidence-Based Practice, Faculty of Health Sciences and Medicine, Bond University, Gold Coast, QLD, 3School of Health and Rehabilitation Sciences, The University of Queensland, 4School of Primary Health Care, Monash University, Melbourne, VIC, 5Allied Health Research Unit, Kingston Centre, Southern Health, Clayton, VIC, AustraliaBackground: Older people are at increased risk of falls after hospital discharge. This study aimed to describe the circumstances of falls in the six months after hospital discharge and to identify factors associated with the time and location of these falls.Methods: Participants in this randomized controlled study comprised fallers (n = 138) who were part of a prospective observational cohort (n = 343) nested within a randomized controlled trial (n = 1206). The study tested patient education on falls prevention in hospital compared with usual care in older patients who were discharged from hospital and followed for six months after hospital discharge. The outcome measures were number of falls, falls-related injuries, and the circumstances of the falls, measured by use of a diary and a monthly telephone call to each participant.Results: Participants (mean age 80.3 ± 8.7 years) reported 276 falls, of which 150 (54.3%) were injurious. Of the 255 falls for which there were data available about circumstances, 190 (74.5%) occurred indoors and 65 (25.5%) occurred in the external home environment or wider community. The most frequent time reported for falls was the morning (between 6 am and 10 am) when 79 (28.6%) falls, including 49 (32.7%) injurious falls, occurred. The most frequently reported location for falls (n = 80, 29.0%), including injurious falls (n = 42, 28.0%), was the bedroom. Factors associated with falling in the bedroom included requiring assistance with activities of daily living (adjusted odds ratio 2.97, 95% confidence interval (CI) 1.57–5.60, P = 0.001) and falling in hospital prior to discharge (adjusted odds ratio 2.32, 95% CI 1.21–4.45, P = 0.01). Fallers requiring assistance with activities of daily living were significantly less likely to fall outside (adjusted odds ratio 0.28, 95% CI 0.12–0.69, P = 0.005).Conclusion: Older patients who have been recently discharged from hospital and receive assistance with activities of daily living are at high risk of injurious falls indoors, most often in the bedroom. These data suggest that targeted interventions may be needed to reduce falls in this population.Keywords: falls, patient discharge, environment, activities of daily living, accident prevention